Professional Surveyors and Real Property Descriptions : Composition, Construction, and Comprehension - Estopinal, Stephen V. (Stephen Vincent) author 216195; Lathrop, Wendy author 204269 (Hoboken, N.J. : John Wiley & Sons, 2012)
"Land boundaries are the physical, technical, and legal entities that define the extent and limits of a particular parcel of land, whether a small acreage of private property or the delineation between sovereign nations. This book is intended to be a tutorial on writing land descriptions for surveyors, allowing readers to be able to construct complete and modern land descriptions. Providing not only information on how to write new descriptions, this book also covers the history of how historic descriptions were written, enabling the reader to properly interpret them today"--